Refugee “In-betweenness”: A Proactive Existence - Manjikian, Lalai (Refuge: Canada’s Journal on Refugees, 2011)
This paper challenges the focus on marginalization that is commonly associated with refugee claimants. By proposing a closer look at the critical period during which refugee claimants residing in Montréal wait for their status to be determined, this paper suggests that “in-betweenness” can be a moment and site that engenders social inclusion. I argue that during the re-settlement process, certain circumstances can foster pathways of agency and engagement as opposed to reproducing cycles of exclusion, commonly associated with refugee claimants that other authors have documented. Drawing on participant narratives, this paper demonstrates how refugee claimants awaiting determination can become active social and political subjects. The paper underscores that in-betweenness, in both temporal and spatial dimensions, can foster a proactive stance despite refugee claimants’ lack of status, limited access to resources, and possibly reduced mobility.